(untitled) (Applied Biological Research, 2022)
Enormous quantities of hazardous coal fly ash (FA), generated by thermal power plants, adversely affect the soil and water quality. The present field experiment, conducted under semi-arid conditions of Bundelkhand (India) in 2018-2019, was aimed to explore the potential use of coal FA in soil along with fertilizer and vermicompost (VC). The experiment comprised of eight treatments i.e. different doses of FA (10, 20, 30, 40 and 50 t ha-1) along with 2 t VC ha-1 and fertilizer (basal dose of NPK), control (no amendment), fertilizer only and VC only. The study revealed that treatment 20 t ha-1 FA + VC + fertilizer had maximum enzymatic activity between 45th to 60th day. Metagenomic study of this treatment showed Betaproteobacteria (22%), Halophaga(17%), Acidimicrobiia (10%) and Nitrosptra (10%) as the most abundant bacterial class, while order Bacillales (22%), Ardenscatenales(16%), Deinococcales (8%) and Actinomycetales (4%). The most abundant orders were Clostridiales (22%), Chroococcales (17%),(10%), and Gemmatimonadales (8%). At family level most abundant were Clostridiaceae (25%), Xenococcaceae (12%) and Pseudoanabaenaceae (8%). The study reveals the reduction in hazardous impact of fly-ash on soil and thereby signifies its potential use to improve the crop yield and quality.